The Influence of emotional labor and emotional intelligence on job performance: Does ownership type matter? A comparison of public and private organizations in China - Ma, S.; Silva, M. G.; Trigo, V.; Callan, V. J. (International Journal of Public Administration, 2020)
Given the limited knowledge about the effect of contextual factors of organizational ownership types on emotional labor, this research addresses two main questions: (1) whether emotional labouror varies among organizations with different ownership types; and (2) whether emotional labor and emotional intelligence relate to job performance in different ways in public and private organizations. This paper exames the research questions with 306 self-report questionaires from the public sector, domestic privately-owned enterprises and foreign-invested firms in China. Significant differences were found in the emotional labor reported in public and private organizations. Overall, emotional labor was found to have a significant effect on in-role performance, and emotional intelligence moderated the link between emotional labor and job performance in public organizations, but not in private organizations.